Huang Ji’s Instrumental Body of Work: at the Origins of the Development of the National Music Culture of the Twentieth Century - Mengmeng Chen (Культура України, 2019)
Problem statement. The relevance of the subject is due to the fact that the renaissance process of Huang Ji’s personality and body of work began in the 1990’s when the effects of the false assessment of the music activity of the Chinese composer as a traitor of national interests formed during the “cultural revolution” were eliminated. The aim of the article is to provide a genre and style analysis of Huang Ji’s instrumental works, appraising their significance in the context of the development of the national music culture of China of the future. Research methodology is based on the method of historicism, axiological and musicological and analytical approaches, and genre and style analysis. Results. The modern interpretation of Huang Ji’s creative personality as the founder of Chinese music culture, based on the introduction of the principles of European professional traditions into the national art, requires an analytical study of the entire building of the works of the composer, in particular, instrumental (symphonic ouverture «In memoriam», orchestral play «Fantastic city», polyphonic piano works Prelude «Subject from Bach», «Two two-part inventions», three fugues in the strict style), which have remained until now outside the interests of Chinese musicologists, who traditionally pay more attention to the vocal creative work of the founder of the national classics of the twentieth century. The study of Huang Ji’s symphony and piano pieces, written during his traineeship at the School of Music in Oberlin (second half of the 1920’s), has made it possible to appraise the historical significance of the Chinese composer as the founder of national instrumental art, Europeanized in origin, based on mastering the classical genres, forms, themes and foundations of composer’s technique. Novelty. An attempt is made at identifying the genre and style features of Huang Ji’s instrumental body of work, based on the traditions of European professionalism, in the fields of symphonic and piano music. The practical significance. The research has important implications for studying the significance Huang Ji’s instrumental body of work in the context of the development of the national music culture of China of the future.